2018
DOI: 10.15252/embj.201798684
|View full text |Cite
|
Sign up to set email alerts
|

Mice with endogenous TDP ‐43 mutations exhibit gain of splicing function and characteristics of amyotrophic lateral sclerosis

Abstract: TDP‐43 (encoded by the gene TARDBP) is an RNA binding protein central to the pathogenesis of amyotrophic lateral sclerosis (ALS). However, how TARDBP mutations trigger pathogenesis remains unknown. Here, we use novel mouse mutants carrying point mutations in endogenous Tardbp to dissect TDP‐43 function at physiological levels both in vitro and in vivo. Interestingly, we find that mutations within the C‐terminal domain of TDP‐43 lead to a gain of splicing function. Using two different strains, we are able to se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
151
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(179 citation statements)
references
References 43 publications
9
151
0
2
Order By: Relevance
“…Although TDP‐43 pathology seems to be a consistent feature in these cases, the pattern of FTLD‐TDP is not consistent, often difficult to classify and may be combined with a more complex proteinopathy . Some of the clinical and pathological variation associated with TARDBP mutations may reflect recent findings that different mutations may have different pathomechanisms, including both loss of function and gain of RNA splicing activity .…”
Section: Ftld‐tdpmentioning
confidence: 95%
“…Although TDP‐43 pathology seems to be a consistent feature in these cases, the pattern of FTLD‐TDP is not consistent, often difficult to classify and may be combined with a more complex proteinopathy . Some of the clinical and pathological variation associated with TARDBP mutations may reflect recent findings that different mutations may have different pathomechanisms, including both loss of function and gain of RNA splicing activity .…”
Section: Ftld‐tdpmentioning
confidence: 95%
“…B TDP-43 intensity in cell nuclei of untransduced or TDP-43 12xQN-infected hippocampal neurons normalized to mean nuclear intensity in untransduced neurons. Two recent studies generated knock-in mice carrying a Q331K substitution, equivalent to a mutation found in human patients, and found mRNA splicing patterns in TDP-43 target genes consistent with enhanced TDP-43 activity, suggesting a gain-of-function mechanism (Fratta et al, 2018;White et al, 2018). Student's ttest; **P < 0.01.…”
Section: Discussionmentioning
confidence: 99%
“…Several animal models have shown that overexpression of TDP-43, wild type or mutant, is in itself toxic in a dosedependent manner and able to produce neurodegeneration, often without formation of aggregates (Baloh, 2011;Arnold et al, 2013), suggesting that TDP-43 inclusions are not necessary to promote neurotoxicity. Two recent studies generated knock-in mice carrying a Q331K substitution, equivalent to a mutation found in human patients, and found mRNA splicing patterns in TDP-43 target genes consistent with enhanced TDP-43 activity, suggesting a gain-of-function mechanism (Fratta et al, 2018;White et al, 2018). Intriguingly, although Q331K knock-in mice showed reduced levels of Sort1 mRNA containing exon 17b, they displayed significantly elevated levels of mutant Tardbp mRNA and TDP-43 protein, by as much as 45% (White et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these results reinforce the importance of the TDP-43 and splicing: mRNA mis-splicing is a common pathological mechanism widely recognized in ALS. In particular, the effects of TDP-43 on RNA metabolism have been extensively studied due to the pivotal role that this protein plays in ALS physiopathology [68]- [72]. TDP-43 mutations are known to induce ALS clinical traits through mRNA missplicing in patients [73], [74].…”
Section: Nf Stoichiometrymentioning
confidence: 99%
“…Depletion of TDP-43 in cell culture can cause the abnormal splicing of cryptic exons and lead to toxicity [75]. Also, mice expressing TDP-43 mutated in its low-complexity domain suffered from neurodegeneration that correlated with the consistent skipping of constitutive exons normally spliced by wild-type TDP-43 (named skiptic exons) [72], [76]. In 2007, the direct stability-mediated effect of TDP-43 on NEFL mRNA was described [77].…”
Section: Nf Stoichiometrymentioning
confidence: 99%